Detection of Tumor-Specific Antigens in an Equine Sarcoid Cell Line - Watson, R. E. (1974)
Indirect immunofluorescence and lymphocyte cytotoxicity experiments demonstrated the presence of a tumor-specific antigen(s) on the surface of cells from an equine sarcoid cell line (Mc1). Autologous serum (taken from the horse from which the Mc1 cells were derived) and sera from three other sarcoid-bearing horses revealed a similar membrane immunofluorescence when reacted with Mc1 cells, indicating the existence of cross-reacting antibodies. Results of serum colony inhibition experiments indicate that these antibodies are not cytotoxic. Incubation of Mc1 cells with autologous lymphocytes resulted in a toxicity to Mc1 cells, thereby demonstrating a cell-mediated immune reaction to autologous tumor cells.